Ethical Leadership and Employee Knowledge Sharing With a Mediation Role Employee Moral Identity - Firmansyah Firmansyah; Adi Rahmat; Muhammad Rasyid Abdillah (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2024)
This study investigates the direct and indirect correlation between ethical leadership and lecturers' knowledge-sharing experiences through the mechanism of moral identity. A quantitative approach was used in this research, involving 95 respondents who were permanent lecturers at Lancang Kuning University. Research findings show that ethical leadership is positively related to the act of sharing knowledge, both directly and through moral identity. In addition, the results also show that ethical leadership is positively related to moral identity, while moral identity itself is positively correlated with knowledge sharing. This study also found that moral identity acts as a mediator in the influence of ethical leadership on knowledge-sharing behavior. This research highlights that ethical leadership, which reflects personality, honesty, reliability, and high morality and understands its impact on others, can model behavior and shape employees' moral construction through moral identity. In essence, this research contributes to the expanding body of literature on organizational behavior by shedding light on the intricate dynamics between ethical leadership, moral identity, and knowledge-sharing behaviors among lecturers. Furthermore, it underscores the practical implications for educational institutions seeking to foster a culture of knowledge-sharing and ethical leadership within their academic community.